Improving Farmers’ Knowledge of Sheep Manure-Based Bokashi Fertilizer in Sukabumi: A Development Communication Approach - Gandasari, Dyah; Gandasari, Aswandi; Bintang; Gandasari, Nurmayanti; Sugiarto, Mochamad; Dwidienawati, Diena (ANIMAL PRODUCTION, 2025)
Sheep farming in Gegerbitung District, Sukabumi Regency, generates a significant amount of feces waste that is not optimally utilized. This study examines the role of development communication in improving farmers' knowledge regarding the innovation of processing sheep manure into bokashi fertilizer. The study aims to (1) assess farmers' knowledge levels on utilizing sheep manure before and after extension activities, (2) analyze differences in knowledge levels between pre- and post-extension periods, and (3) examine the relationship between farmers' characteristics and their knowledge improvement. This research employs a quantitative pre-test and post-test design involving 117 sheep farmers selected through purposive sampling from five farmer groups. Data were collected using structured questionnaires and analyzed using descriptive analysis, the Wilcoxon signed-rank test, and Spearman's rank correlation. The results indicate a significant increase in farmers' knowledge after the extension activities. The Wilcoxon test yielded a p-value of 0.000 (p < 0.05), confirming a significant difference in knowledge levels before and after the training. Spearman's correlation analysis showed a positive relationship between age and knowledge level (rs = 0.190, p < 0.05), while the number of livestock owned had a negative correlation with knowledge level (rs = −0.314, p < 0.01). These findings highlight the effectiveness of development communication in facilitating knowledge transfer among farmers. The study suggests that future extension programs, in addition to addressing labor and time constraints, should be tailored to the demographic characteristics of farmers to enhance the adoption of sustainable waste management innovations